Privacy of Appealing Against Decisions of Endless Dispute - Jasim Mohammed, Lect. Ali (Basra studies journal, 2024)
Competent courts exercise many tasks in accordance with the discretionary authority granted to them by the legislator. Among those tasks are issuing judicial decisions related to the progress of the case or matters of proof, which help in resolving the merits of the case. Given the connection of the fate of those decisions to the final ruling issued on the merits of the case, the procedural laws Including the Iraqi Civil Procedure Law No. 83 of 1969 (the amended), and the Egyptian Civil and Commercial Procedure Law No. 13 of 1968. It dealt with the issue of appealing these decisions, especially the appeal, independently of the final ruling. It decided on a general principle stipulating that it is not permissible to appeal, with some exceptions that It has justification for the permissibility of appealing it on its own, and the appeal against it was characterized by a kind of privacy that accompanied the provisions regulating the appeal of these decisions.